Madame Curie : a biography - Curie, Eve, 1904-2007.; Sheean, Vincent, 1899-1975. (New York : Pocket Books, 1937)
This story was published serially under the title Marie Curie, my mother ; p. [1].
Includes index.
Jerome P. Webster Library of Plastic Surgery.
Keywords: Curie, Marie, -- 1867-1934. -- Biography